State, Refugees, and Civil Society in Turkey: Transformation Under Control - Birce Altıok (Alternatif Politika)
The forced migration movement from Syria, which began in 2011, has brought about significant changes in civil society within Turkey. The already existing complex relationship between the state and civil society, is further diversified in the context of forced migration, presenting the need to focus on the provision of humanitarian assistance, access to services, and integration of Syrian refugees who are legally under temporary protection, without international refugee recognition. Furthermore, state-driven cross-border humanitarian operations and security-oriented state policies also shape this landscape. Therefore, the interplay between civil society actors –existing, government-supported, and newly emerging– and security-oriented state policies contributes to this transformation. Historical and political realities, alongside global-local crises, influence the trajectory of change within civil society, positioning authorities as pivotal decision-makers in managing individuals’ movement. Through in-depth interviews in different cities of Turkey with NGOs and refugee-led civil society members in 2018, the article uncovers the formation and progression of relationships between civil society actors and the state, revealing adaptations and adjustments based on contextual circumstances. The article seeks to move beyond comprehensive liberal and developmental perspectives, instead focusing on the evolving dynamics of state control within migration-related civil society.